Black Girls and Dolls Navigating Race, Class, and Gender in Toronto. Issue 2 (1st July 2019) - Seow, Janet
Abstract : Doll play is critical in the formation of young black girls' gender, race, and class identities. In this article, I use textual analysis that emphasizes how physical changes in dolls correspond to contextual shifts in society over the last seven decades, and qualitative research with ten Afro-Caribbean girls and young women in Toronto to reveal the racial and cultural meanings of dolls in young people's everyday lives and how doll play is complicated by racist and classist representations of dolls. By exploring what doll play meant to them, I show how it helps black girls understand racial and gendered norms. Through doll play, girls reveal an understanding of their racialized identities and marginalization as they demonstrate unacknowledged skills in their ability to navigate barriers that reinforce racial inequalities and social hierarchies in girls' material culture in a multicultural Toronto.